2021
DOI: 10.1681/asn.2021050689
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-Engineered HLA-Deleted Glomerular Endothelial Cells as a Tool to Predict Pathogenic Non-HLA Antibodies in Kidney Transplant Recipients

Abstract: BackgroundAfter kidney transplantation, donor-specific antibodies against human leukocyte antigen donor-specific antibodies (HLA-DSAs) drive antibody-mediated rejection (ABMR) and are associated with poor transplant outcomes. However, ABMR histology (ABMRh) is increasingly reported in kidney transplant recipients (KTRs) without HLA-DSAs, highlighting the emerging role of non-HLA antibodies (Abs).MethodsW e designed a non-HLA Ab detection immunoassay (NHADIA) using HLA class I and II–deficient glomerular endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…The discovery of new targets for non-HLA antibodies is an ongoing process ( 4 , 19 , 43 49 ). Although several non-HLA antibody specificities have been identified, the currently available solid-phase assays are limited to the known non-HLA antigens ( 23 , 50 ). Only antibodies directed against TUBB4B were found to be present in the serum of the patient described here; however, this antibody has never been described to correlate with rejection or graft failure ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of new targets for non-HLA antibodies is an ongoing process ( 4 , 19 , 43 49 ). Although several non-HLA antibody specificities have been identified, the currently available solid-phase assays are limited to the known non-HLA antigens ( 23 , 50 ). Only antibodies directed against TUBB4B were found to be present in the serum of the patient described here; however, this antibody has never been described to correlate with rejection or graft failure ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lamarthée et al. recently described the relevance of a tool to identify pathogenic non-HLA antibodies in kidney transplant recipients by utilizing CRISPR/Cas9-engineered HLA-silenced glomerular endothelial cells ( 50 ). Their endothelial crossmatch test identifies non-HLA Abs and strongly predicts graft endothelial injury, independent of HLA-DSAs.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of the NHADIA in an unselected cohort of 389 kidney transplant recipients revealed that preformed non-HLA antibodies were increased in the patients who had undergone previous kidney transplantation, supporting the role of allosensitization to minor histocompatibility antigens. The pretransplant NHADIA value correlated with MVI lesions on the kidney graft at 3 months and 12 months and was associated with the risk of developing ABMRh ( 102 ).…”
Section: Non-hla Antibody-dependent MVImentioning
confidence: 99%
“…Finally, it is still unclear whether a single non-HLA antibody can have a significant impact on graft outcome or whether a combination of several non-HLA antibodies is needed, perhaps with a set of specific antibodies for each individual, therefore requiring potential full sequencing of every donor/recipient pair ( 105 ). One approach may be to develop assays allowing us to detect the burden of non-HLA antibody binding to target cells, as we did with our NHADIA ( 102 ).…”
Section: Non-hla Antibody-dependent MVImentioning
confidence: 99%
“…Salp20 has been shown to inhibit the AP via the displacement of properdin causing an accelerated decay of the C3bBb complex and subsequent inhibition of the AP up t0 70%. 49,50 However, no experiments have been performed yet in inhibiting the AP activation on a renal cellular level.…”
Section: Table 1 the Involvement Of Complement In Kidney Diseasesmentioning
confidence: 99%